Retention Curves for Pediatric and Neonatal Intubation Skills After Simulation-Based Training. Issue 2 (February 2016) - Andreatta, Pamela B.; Dooley-Hash, Suzanne L.; Klotz, Jessica J.; Hauptman, Joe G.; Biddinger, Bea; House, Joseph B.
Abstract : Objectives: We evaluated the retention of pediatric and neonatal intubation performance abilities of clinicians trained on a simulated or live tissue model at 3 intervals after initial training to assess competency degradation related to either training modality or retention interval. Methods: We implemented a quasi-experimental design with purposive sampling to assess performance differences between 171 subjects randomly assigned to 1 of 3 intervals after initial training: 6 weeks, 18 weeks, or 52 weeks. Training followed the American Heart Association Pediatric Advanced Life Support and Neonatal Resuscitation Program protocols with hands-on practice using 1 of 2 models (live feline or simulated feline). Assessment data were captured using validated instruments and analyzed using analysis of variance with repeated measures (statistical significance set at P < 0.05). Results: Cognitive retention scores decreased significantly ( P = 0.000) from posttraining cognitive scores. There were no significant differences between posttraining and retention scores for pediatric and neonatal performances. Both affect and self-efficacy retention scores decreased significantly ( P = 0.000) from posttraining scores at 18 and 52 weeks, but remained constant at 6 weeks. Retention scores for all dimensions showed a significant difference between subjects with varying amounts of experience performing pediatric and neonatal intubation, such that those with more experience scored higher those with less ( P < 0.003). Conclusions: Retention performance outcomes decreased sufficiently from posttraining scores to suggest that training refreshment could serve to maintain posttraining competency in the ability to perform pediatric and neonatal intubation. Retraining intervals may be best aligned with provider experience levels. Future research focusing on the effect of variable interval refresher training on retention in pediatric and neonatal intubation is merited.